Phenotype correlation analysis and excellent germplasm screening of herb Bletilla Rchb. f. based on comprehensive evaluation from thirty-three geographic populations - Huang, Junfeng; Yuan, Fang; Zhou, Ming; Huang, Tianyue; Zhang, Yanjun; Liang, Qiong (BMC plant biology, 2022)
The Bletilla genus of Orchidaceae includes plants with great economic value, among which B. striata is the main traditional medicinal plant, and its pseudobulb, known as BaiJi, was first recorded in Shennong's Classic of Materia Medica. However, there has been little systemic evaluation of the germplasm quality of Bletilla plants in China. In order to comprehensive evaluate the Bletilla resources in China and screen out the candidate phenotypic traits determining yield and/or quality of Bletilla, the variation of phenotypic indicators (pseudobulb, leaf, stem, inflorescence, flower) and active ingredients contents (polysaccharide, total phenolics and militarine) in different populations of B. striata and B. ochracea were investigated through 4 years' common-garden experiment. There were abundant phenotypic variations and significant differences among different populations in the morphological phenotypes, pseudobulb weight and main active ingredient contents. AHBZ, HBLT and HBSN populations showed good prospects for industrial development, presenting higher quality in terms of yield and main active ingredient content. Pseudobulb yield, polysaccharide and total phenol content are positively correlated with phenotypic traits. Militarine content is negatively correlated with almost all indexes. Plant height, leaf width and stem diameter may be important indicators of potential excellent germplasms. Bletilla is not strictly geoauthentic medicinal plants. B. ochracea could be accepted as an alternative resource to B. striata. The best harvest period of Bletilla is the third year after cultivation. Plant height, leaf width and stem diameter may be important indicators of potential excellent germplasms. These results provide important information required for the efficient screening and utilization of Bletilla germplasm resources.